Phenotypic diversity of coconut germplasm conserved at different stations of BARI (Bangladesh Journal of Agricultural Research, 2010)
Diversity of coconut germplasm being conserved at different Regional and Sub-stations of the Bangladesh Agricultural Research Institute (BARI) was estimated during 2001-2002. Diversity indices (D2) ranged from 1068.96 to 171.93. Maximum diversity was observed between BARI Narikel-2 and Rahmatpur Yellow Dwarf. Genotypes of Regional Agricultural Research Station, Jessore and BARI Narikel-2 were found morphologically similar. Population under conservation at Jamalpur and lshwardi stations were found close to BAR! Narikel-l. Similar relationships among the genotypes were reflected when they were grouped into several clusters. Out of six clusters, the members of cluster II were homogenous, while that of cluster IV showed heterogenicity.Key Words: Phenotypic diversity; coconut germplasm.DOI: 10.3329/bjar.v34i1.5749Bangladesh J. Agril. Res. 34(1) : 25-31, March 2009